1991
DOI: 10.1172/jci115495
|View full text |Cite
|
Sign up to set email alerts
|

Active site-blocked factor IXa prevents intravascular thrombus formation in the coronary vasculature without inhibiting extravascular coagulation in a canine thrombosis model.

Abstract: To assess the contribution of Factor IX/IXa, to intravascular thrombosis, a canine coronary thrombosis model was studied. Thrombus formation was initiated by applying current to a needle in the circumflex coronary artery. When 50% occlusion of the vessel developed, the current was stopped and animals received an intravenous bolus of either saline, bovine glutamylglycyl-arginyl-Factor IXa (IXai), a competitive inhibitor of Factor IXa assembly into the intrinsic Factor X activation complex, bovine Factor IX, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
62
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 24 publications
4
62
0
Order By: Relevance
“…These studies thus extend previous studies reporting antithrombotic efficacy of FIXai in canine models of arterial thrombosis and cardiopulmonary bypass surgery. 17,27 Preliminary studies conducted in our laboratory also demonstrate that treatment with BC2 results in extended patency of the blood vessel; thus a single bolus injection of BC2 not only increased the incidence of vessel patency 60 minutes after BC2 administration but also 24 hours later at a time when aPTT was within normal range. This phenomenon may reflect the capacity of the vessel wall to initiate repair when coagulation is interrupted at FIX/IXa limiting the generation of factor Xa and thrombin.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…These studies thus extend previous studies reporting antithrombotic efficacy of FIXai in canine models of arterial thrombosis and cardiopulmonary bypass surgery. 17,27 Preliminary studies conducted in our laboratory also demonstrate that treatment with BC2 results in extended patency of the blood vessel; thus a single bolus injection of BC2 not only increased the incidence of vessel patency 60 minutes after BC2 administration but also 24 hours later at a time when aPTT was within normal range. This phenomenon may reflect the capacity of the vessel wall to initiate repair when coagulation is interrupted at FIX/IXa limiting the generation of factor Xa and thrombin.…”
Section: Discussionmentioning
confidence: 83%
“…15 Lollar and Fass 16 showed that active-site blocked factor IXa (FIXai) inhibits clot formation in vitro. Benedict et al demonstrated that administration of FIXai prevents thrombosis in experimental animal models, 17 indicating that modulation of FIX function can be achieved to gain therapeutic efficacy in thrombosis. Bajaj and coworkers 18 have described antibody mediated inhibition of FIX coagulant activity but did not explore in vivo application of the antibody as an antithrombotic agent.…”
mentioning
confidence: 99%
“…sLA-LMWH can be added to a growing list of enzyme complex inhibitors, which include active site blocked f.Xa and f.IXa (51,52), f.IXa antibodies (53), and active site directed f.Xa inhibitors (54 -57). sLA-LMWH may have advantages over other agents because it simultaneously attenuates f.Xa and thrombin generation, with selectively greater inhibition of f.Xa generation by intrinsic tenase.…”
Section: Sla-lmwh Inhibits Intrinsic Tenase and Prothrombinasementioning
confidence: 99%
“…1 Therefore, one may infer that an approach to treat thrombotic disorders by interfering with F.IXa function would have an unacceptable bleeding liability. Yet, Benedict et al 2 were able to demonstrate that short-term inhibition of F.IXa function by active site-blocked F.IX (F.IXai) can be safe as well as effective in preventing thrombus formation in a canine model of electric currentinduced thrombosis. Subsequent in vivo studies with the prototypic inhibitor F.IXai further corroborated this paradigm, 3,4 indicating that the specific targeting of F.IXa activity could represent a promising therapeutic strategy.…”
mentioning
confidence: 99%
“…8,9,13 Based on the structural requirements for intrinsic Xase assembly, new approaches to specifically interfere with F.IXa activity are conceivable. To this end, we used a F.IX-Gla domain-directed phage display strategy to generate the antibody 10C12, a fully humanized F(abЈ) 2 that specifically binds to the Gla domain of F.IX/IXa. 14 In addition to inhibiting platelet-dependent intrinsic Xase activity, 14 10C12 was found to block F.IX activation by F.XIa and by the tissue factor:F.VIIa (TF:F.VIIa) complex.…”
mentioning
confidence: 99%